Fermentation characteristics and nutritive value of sweet sorghum silage with Paiaguas palisadegrass and Ipypora grass - Oliveira, Nariane Coelho de; Costa, Kátia Aparecida de Pinho; Rodrigues, Laíne Gonçalves; Silva, Ana Carolina Gomes; Costa, João Victor Campos Pinho; Silva, Sabryna Álex Almeida; Assis, Luiz Felipe Aprígio de; Oliveira, Stella Mendes Pio de; Vieira, Milena de Lima (Semina: Ciências Agrárias, 2021)
Ensiling sorghum with tropical forages has been shown to be a promising alternative for ruminant feed production, as this approach improves the quality of the sorghum silage. In this context, the goal of this study was to evaluate the fermentation characteristics and nutritive value of sweet sorghum silage made with different levels of Paiaguas palisadegrass and Ipypora grass. The experiment was conducted in a completely randomized 2 x 6 factorial design with four replications. Two forages (Paiaguas palisadegrass and Ipypora grass) were added to sorghum at six levels (0, 20, 40, 60, 80 and 100%), for a total of 48 experimental silos. After 50 days of fermentation, the silos were opened, and the fermentation profile and chemical composition of the silage were analysed. The results showed that the addition of Paiaguas palisadegrass and Ipypora grass to the sorghum silage increased the pH, buffering capacity and NH3-NT of the silage and reduced its dry matter content but did not affect its fermentation characteristics, which remained within an appropriate range. The addition of increasing levels of Paiaguas palisadegrass and Ipypora grass to the sorghum silage increased the crude protein and in vitro dry matter digestibility (IVDMD) of the silage and decreased the fibre fraction (neutral detergent fibre, acid detergent fibre and lignin) and ether extract contents. Adding tropical forages to sorghum silage material at levels above 40% is recommended. Among forage crops, addition of Paiaguas palisadegrass to sorghum silage resulted in higher content of crude protein and IVDMD. Mixed silages can be an effective alternative to improve the quality of forage sorghum silage.